Cover Picture: Should the Woodward–Hoffmann Rules be Applied to Mechanochemical Reactions? (ChemPhysChem 8/2015). Issue 8 (8th June 2015) - Wollenhaupt, Miriam; Krupička, Martin; Marx, Dominik
Abstract : By analyzing the Woodward–Hoffmann‐allowed and ‐forbidden reaction pathways of a cyclopropane derivative as a function of the applied force, M. Wollenhaupt et al. show, onp. 1593, that the electronic structure is not significantly changed along both reaction pathways that are systematically distorted as a result of the applied mechanical force. It is rather the mechanical work term that modifies the corresponding activation energies to eventually energetically favor the product that is not expected from applying the Woodward‐Hoffmann rules. Thus, these rules, which were derived for thermal and photochemical activation, cannot be applied to mechanochemical activation, and therefore, one should not speak about their "violation". Instead, one needs to think of mechanochemical reactions evolving on what we call "force‐transformed potential energy surfaces".